Effects of experimental domestication of silver foxes (Vulpes vulpes) on vocal behaviour - S. S. Gogoleva; I. A. Volodin; E. V. Volodina; A. V. Kharlamova; L. N. Trut (Вавиловский журнал генетики и селекции, 2017)
This paper systematizes and generalizes a research cycle devoted to studying the acoustics and vocal behaviour of silver foxes that differ in their tolerance to humans. The research revealed that 50-year selection for tameness toward people resulted in selective use by Tame foxes toward humans of two call types, pant and cackle. At the same time, the selected for aggression toward people Aggressive foxes and the non-selected for behaviour Control foxes, selectively use toward humans cough and snort. Thus, call types representing vocal indicators of friendly and aggressive behaviour of foxes toward humans have been revealed by the research. Nevertheless, experimental domestication did not change vocal behaviour of foxes toward conspecifics; all three strains did not differ by their vocal behaviour toward same-strain silver foxes. Relationship has been investigated between vocal behaviour and degree of tolerance toward people for hybrids between Tame and Aggressive foxes and for backcrosses to Tame and Aggressive foxes. Effect was estimated between fox sex and the degree of human impact on focal fox for variables of fox vocal behaviour. The research revealed the universal for mammals vocal indicators of emotional arousal that are independent of the emotional valence. Characteristics of vocal behaviour that are related with positive and negative emotional valence have been revealed. A simple and effective method for estimating animal discomfort based on ”joint calls” that takes into account the characteristics of all calls irrespective of their acoustic structure has been revealed. The obtained results provide a basis for further comparative studies of the acoustic structure and vocal behaviour for other taxa of the genus Vulpes and the related canid genera (Canis, Cuon, Lycaon).